2018
DOI: 10.1002/cphc.201800094
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic/Anisotropic NMR Editing by Resolution‐Enhanced NMR Spectroscopy

Abstract: Modern resolution-enhanced NMR techniques can monitor the in situ discrimination of co-existing isotropic and anisotropic contributions of small molecules dissolved in weakly aligning PMMA/CDCl3 media. The simultaneous sign-sensitive determination of accurate Δδ ( H), Δδ ( C) and/or isotropic J and anisotropic T coupling constants (and consequently H- C residual dipolar couplings and H/ C residual chemical shift anisotropies) can be performed from spectral-aliased heteronuclear single-quantum correlation spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Recently, a method employing self-assembling polypeptides was reported that allowed for the measurement of the 13 C NMR spectrum in an isotropic state, and then after an equilibration time ranging from hours to weeks, a complementary 13 C spectrum could be acquired in an aligned condition . Work in the Gil lab demonstrated that RDCs can be measured in a single experiment when using compressed gels due to the fact that after a certain degree of compression, the gels buckle and generate pockets of isotropic solvent, which are never eliminated. , The amount of buckling depends on the degree of polymeric cross-linking and the length of the gel …”
mentioning
confidence: 99%
“…Recently, a method employing self-assembling polypeptides was reported that allowed for the measurement of the 13 C NMR spectrum in an isotropic state, and then after an equilibration time ranging from hours to weeks, a complementary 13 C spectrum could be acquired in an aligned condition . Work in the Gil lab demonstrated that RDCs can be measured in a single experiment when using compressed gels due to the fact that after a certain degree of compression, the gels buckle and generate pockets of isotropic solvent, which are never eliminated. , The amount of buckling depends on the degree of polymeric cross-linking and the length of the gel …”
mentioning
confidence: 99%
“…Before acquiring the RDC data, the quadrupolar splitting of CD 2 Cl 2 in each sample was measured to ensure similar ordering strength among the samples. In addition to measuring the 1 D CH data using the aforementioned CLIP-HSQC experiment, we also extracted the same data using the F1 dimension J -scaled BIRD HSQC (JSB-HSQC) pulse sequence, which is better suited for more complex compounds containing several methylene groups. …”
Section: Resultsmentioning
confidence: 99%